2010
DOI: 10.1007/s11357-010-9160-x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in short tandem repeats deduced on the basis of the number of repeats and the relationship of these variations with longevity

Abstract: The objective of this study was to investigate the quantitative characteristics of short tandem repeat (STR) variations deduced on the basis of the number of STRs that are beneficial for human survival. The longevity group included 60 nonagenarian subjects, and the control group included 250 reference adults (age, 20-50 years). Alleles of 15 Combined DNA Index System STR loci were determined using a commercial polymerase chain reaction kit. An STR with the highest frequency distribution in a population (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…On the other hand, the statistical power analysis suggested that the study had enough power (>0.8) to detect an OR value of 1.5 or above, when risk alleles frequency was ≥0.1 (i.e., the frequency of allele 11 in D22S1045), or an OR value of 1.7, when risk allele frequency was ≥0.05 (i.e., the frequency of allele 17 in D12S391 or allele 15 in D2S441) (see Supplementary Table S1). Specifically for alleles 9.3+10 in THO1 (previously associated with longevity by Tan et al 2002 but without a significant association in our study) and allele 10 in CSF1PO (previously related to longevity by Hui et al 2011 and with a borderline significant trend in our study), statistical power calculations indicated that given the frequency of these alleles in controls (0.312 and 0.315, respectively) (Supplementary Table S3), we would have a power of 87 % to detect an OR≥1.35.…”
Section: Resultscontrasting
confidence: 50%
See 2 more Smart Citations
“…On the other hand, the statistical power analysis suggested that the study had enough power (>0.8) to detect an OR value of 1.5 or above, when risk alleles frequency was ≥0.1 (i.e., the frequency of allele 11 in D22S1045), or an OR value of 1.7, when risk allele frequency was ≥0.05 (i.e., the frequency of allele 17 in D12S391 or allele 15 in D2S441) (see Supplementary Table S1). Specifically for alleles 9.3+10 in THO1 (previously associated with longevity by Tan et al 2002 but without a significant association in our study) and allele 10 in CSF1PO (previously related to longevity by Hui et al 2011 and with a borderline significant trend in our study), statistical power calculations indicated that given the frequency of these alleles in controls (0.312 and 0.315, respectively) (Supplementary Table S3), we would have a power of 87 % to detect an OR≥1.35.…”
Section: Resultscontrasting
confidence: 50%
“…Given that some of these STR loci correlate with physical traits, it has been speculated that they could confer additional information that could reveal genetic traits or predispositions for inherited diseases of a given individual. Specifically regarding human life span, the forensic STRs HUMTHO1 (THO1) and HUMCSF1PO (CSF1PO) have been previously linked to human longevity (De Benedictis et al 1998;Tan et al 2002;von Wurmb-Schwark et al 2011, Hui et al 2011. The THO1 STR (11p15.5) is located within the first intron of the tyrosine hydroxylase 1 gene (THO1), the rate-limiting enzyme for synthesis of catecholamines, amino acid-derived molecules produced by the sympathetic nervous system in response to stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is also a typically complex process to which a hitherto unknown number of genes contribute by interacting with each other and the external factor [28][29][30]. Here, "external factor" refer to any cause that is not inherited genetically.…”
Section: Introductionmentioning
confidence: 99%